Characterization of ZrO2-Montmorilonite Pillarization Process from Local Zirconium Oxychloride Local Made PSTA-BATAN - Muzakky Muzakky; Herry Poernomo (Universitas Gadjah Mada, 2018)
Characterization of the pillarization process product of ZrO2-montmorillonite from Zirconium oxychloride local made of PSTA-BATAN has been done. The objective of this research is to control the quality of pillarization process product of the new material ZrO2-montmorilonite. This new material was produced from local made Zirconium oxychloride (ZOC) of PSTA-BATAN by dry process and bentonite (Na-montmorillonite) imported from Thailand by the pillarization process. During optimization the pillarization quality control would be followed by absorbance using Diffuse Reflectance Ultraviolet-Visible (UV-Vis DRS) spectroscopy and X-Ray Diffraction (XRD). While the type of functional group can be detected by Fourier Transform Infrared (FTIR) spectrophotometry, and the surface image was observed by using Transmission Electron Microscopy (TEM) and BET methods. The result gained showed that the optimum quality of ZrO2-montmorillonite was at Zr concentration of 0.2 M with the absorbance of 1.04 au by XRD and DRS. The best precursor used was ethylene glycol with a drying process in the cold conditions at the absorbance of 1.2 au. The best calcination process was at the temperature of 600 °C with the reached absorbance value of 1.3 au. The results of TEM image observation after calcination at the temperature of 600 °C were clearer and more porous than before and showed specific surface area of 105 m2/g. The interpretation results of FTIR spectra on the new material of ZrO2-montmorillonite contained the cluster of ΞSi-OH, ΞAl-OH and Si-O functional groups indicating pillar groups.